Genome-Wide Identification of APETALA2/ETHYLENE RESPONSIVE FACTOR Transcription Factors in Cucurbita moschata and Their Involvement in Ethylene Response - Li, Qingfei; Zhang, Li; Chen, Peiwen; Wu, Chunhui; Zhang, Huaixia; Yuan, Jingping; Zhou, Junguo; Li, Xinzheng (Frontiers in Plant Science, 2022)
APETALA2/ETHYLENE RESPONSIVE FACTOR (AP2/ERF), a plant-specific transcription factor family, plays an essential role in the growth and development of plants, and in their response to biotic and abiotic stresses. However, information on AP2/ERF in Cucurbita moschata (pumpkin), an edible and medicinal vegetable used worldwide, is scarce. A total of 212 AP2/ERF genes were identified in the C. moschata genome (CmoAP2/ERFs). Based on phylogenetic analysis, they were divided into four groups—28 AP2s, 92 ERFs, 86 dehydration-responsive element-binding (DREB) factors, and 6 ABI3/VPs (RAV). The 212 AP2/ERF genes were unevenly distributed on the 20 chromosomes of C. moschata. The results of structural analysis showed the absence of introns on 132 CmoAP2/ERFs. Four pairs of tandem duplication and 155 pairs of segmental duplication events were identified, which indicated that segmental duplications might be the main reason for the expansion of the CmoAP2/ERF family. The analysis of cis-regulatory elements (CREs) showed that most of the CmoAP2/ERFs contained hormone response elements (ABREs, EREs) in their promoters, suggesting that AP2/ERFs could contribute to the processes regulated by ethylene and abscisic acid. By comparing the transcriptome of ethephon-treated and control plants, we found that 16 CmoAP2/ERFs were significantly upregulated after ethephon treatment. Furthermore, we determined the expression patterns of these genes at different developmental stages of female and male flowers. This study provides insights into the identification, classification, physicochemical property, phylogenetic analysis, chromosomal location, gene structure, motif identification, and CRE prediction of the AP2/ERF superfamily in C. moschata. Sixteen CmoAP2/ERF genes were identified as ethylene-inducible genes. The results of this study will be valuable for understanding the roles of CmoAP2/ERFs in ethylene response and should provide a foundation for elucidating the function of AP2/ERF transcription factors in C. moschata.